Efeito da fotobiomodulação na expressão de NK1 e na alodinia em modelo de tendinite induzida por colagenase - Piccirillo, Soraya (2017)
Tendinopathys is a disturbance in tendon health which, in addition to inflammation, causes a lot of pain and movement limitation, being frequent and difficult to treat. The most widely used treatment today is the pharmacological treatment for pain relief, but with unsatisfactory results due to its side effects in prolonged use. In this context, the search for therapies mainly non-pharmacological in the treatment of tendinitis, assumes important role in the health area. Photobiomodulation has been used in joint diseases with analgesic effects. However the mechanism of action has not yet been fully elucidated. The objective of this work was to evaluate the effect of photobiomodulation on the expression of neurokinin NK1, COX-2, inflammatory infiltrate and mechanical allodynia. Thirty-two male Wistar rats were used. The animals were anesthetized with intraperitoneal injection of ketamine hydrochloride and Xilasina (90mg / kg and 10mg / kg) and were divided into 4 groups: CTL (Control), NT (Tendonitis Untreated), DIC (Tendonitis treated with Sodium Diclofenac IP) and L3J (830nm laser treated tendinitis, 3J, 100mW). Groups NT, DIC and L3J received 100 μl of transcutaneous injection of collagenase (1mg / ml) in the same region of the calcaneus tendon. The allodynia test was performed after 24 hours of tendinitis induction. Then the animals were euthanized and the tendon removed for histological and biochemical analysis. Results: Greater inflammatory infiltrate was observed in the NT group, compared to the DIC and L3J groups. There was an increase in the protein expression of COX-2 and NK1 in the NT group and a decrease in the DIC and L3J groups. Mechanical allodynia presented a greater alteration in the NT group compared to the treated groups (DIC and L3J). Conclusion: Photobiomodulation (830nm, 100mW, 3J), used in the treatment of collagenase-induced tendinitis in rats, was effective in improving nociceptive allodynia and modulating COX-2 and NK1 protein expression, also demonstrating a decrease in inflammatory infiltrate.